ENHANCING CASHEW (Anacardium occidenatale) SEEDLING GROWTH: THE ROLE OF POLYTHENE BAG SIZE ON GERMINATION AND DEVELOPMENT - Abdullahi, Ahmed; Usman, Ahmed; Bukar, Yunusa M.; Umar, Usman A. (FUDMA Journal of Sciences, 2025)
This study investigated the impact of various polythene bag sizes on the germination and growth of cashew seedlings. Three polythene bag sizes (small: 6x9 inches, medium: 8x12 inches, and large: 10x15 inches) were used as treatments, with 15 replications each. The experiment was conducted in a completely randomized design at the Research and Experimental Station, College of Horticulture, Dadin-Kowa, Gombe State, Nigeria. Results showed that the small polythene bag size had the shortest germination day (16.25 days) and highest germination percentage (37.0%) with no significant difference were observed among the treatment in term of germination date and germination percentage. In addition, the large polythene bag size promoted better seedling growth, with significant improvements in plant height, number of leaves, and leaf area. However, no significant difference at (p
Keywords: Polythene Bag Size; Germination; Seedling Growth; Nursery Management